2022
DOI: 10.3389/fmed.2022.804834
|View full text |Cite
|
Sign up to set email alerts
|

Two Compartment Evaluation of Liver Grafts During Acellular Room Temperature Machine Perfusion (acRTMP) in a Rat Liver Transplant Model

Abstract: BackgroundSubnormothermic machine perfusion (SNMP) of liver grafts is currently less clinically developed than normothermic and hypothermic approaches, but may have logistical advantages. At intermediate temperatures, the oxygen demand of the graft is low enough to be satisfied with an acellular perfusate, obviating the need for oxygen carrying molecules. This intermediate metabolic rate, however, is sufficient to support the production of bile, which is emerging as an important indicator of graft injury and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…After 3–5 min, the portal vein was clamped with a microsurgery vascular clamp and the hepatic artery was ligated with 7-0 ties and divided to induce warm ischemic time. After 30 min, the donor liver was procured as previously described 11 and prepared for implant via a modified vascular cuff technique. 12 Preparation of the liver graft was performed at ambient temperature, rather than on ice, to account for the last 15 min of warm ischemia time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After 3–5 min, the portal vein was clamped with a microsurgery vascular clamp and the hepatic artery was ligated with 7-0 ties and divided to induce warm ischemic time. After 30 min, the donor liver was procured as previously described 11 and prepared for implant via a modified vascular cuff technique. 12 Preparation of the liver graft was performed at ambient temperature, rather than on ice, to account for the last 15 min of warm ischemia time.…”
Section: Methodsmentioning
confidence: 99%
“…The liver was then transplanted into the recipient using the modified vascular cuff technique as we have previously described. 11 The bile duct anastomosis was performed using a stent between the recipient and donor bile ducts. No hepatic artery anastomosis was performed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, other groups such as ( 187 , 188 ) have illustrated the efficacy of optimizing the balance between metabolic demand (controlled by temperature) and oxygenation level of the perfusate. In doing so, they have introduced a modality termed subnormothermic machine perfusion (SNMP): perfusion of an organ at room temperature (21°C), in an effort to keep the organ metabolizing at a level sufficient to allow assessment and treatment while keeping its demand for oxygen low enough to prevent IRI injury ( 187 ). This also allows for the use of an acellular perfusate, which is more readily available than blood based perfusates.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…In the clinical trial, HMP was demonstrated to be a safe and feasible option, with potential superiority to SCS in terms of liver injury and postoperative complications (5). Since then, several experimental studies, along with a handful of clinical trials, have aimed to demonstrate the superiority of dynamic preservation methods-MP systems-in the reduction of ischemia reperfusion injury of the liver graft when compared to SCS (6)(7)(8)(9). Thus, under the premise of reducing graft injury before transplantation, research efforts have been toward the evaluation of the potential role of MP as a pathway to lessen the unfavorable shortage of liver organs by increasing the usage of all available organs.…”
Section: Introductionmentioning
confidence: 99%